(untitled) (Journal of actual problems of jurisprudence, 2018)
A comparison of matrimonial property regimes across jurisdictions is of high theoretical and practical interest. In this article the authors characterize, classify, and analyze legal property regimes in Kazakhstan and other countries. The authors offer a brief historical explanation for the variety of property regimes, and for Kazakhstan’s selection of a joint common property regime. The article discusses the consequences of changing a legal regime into another by entering into a marriage contract. The authors describe in detail each of the possible contractual property regimes, weighing their advantages and disadvantages, in particular in light of the possibility of incorporating elements of these regimes into a marriage contract. Key words: property regimes, property relations, property of spouses, joint common property, marriage contract.